Modelling Spray Pressure Effects on Droplet Size Distribution from Agricultural Nozzles - Emanuele Cerruto; Giuseppe Manetto; Rita Papa; Domenico Longo (Applied Sciences, 2021)
For spray applications, drop size is the most important feature as it affects all aspects of a phytosanitary treatment: biological efficacy, environmental pollution, and operator safety. In turn, drop size distribution depends on nozzle type, liquid properties, and working pressure. In this research, three nozzles were studied under ordinary working conditions and the effect of pressure on drop size distribution was assessed. The nozzles under test, all from Albuz (France), were an orange hollow cone nozzle ATR 80 (European color code), an air induction flat spray nozzle AVI 11003, and an air induction hollow cone nozzle TVI 8002. The ATR 80 and the TVI 8002 nozzles were tested at four pressure values: 0.3, 0.5, 1.0, and 1.5 MPa; the AVI 11003 nozzle was tested at 0.3 and 0.5 MPa. The drop size measurement technique was based on the liquid immersion method by using a custom-made test bench; spray quality parameters were computed by means of suitable functions written in R language. Results showed that an increase in working pressure caused an increase in drop pulverization regardless of the type of nozzle, and drop pulverization was higher for the turbulence nozzle than for the two air induction nozzles. Based on skewness and kurtosis values, the theoretical gamma distribution was the most adapt to fit the experimental data. The scale parameter showed a decreasing trend with the increase in the pressure, a clear index of higher drop pulverization.